Kompetensi Teknologi Informasi dan Komunikasi Perguruan Tinggi - Harjanto Prabowo (Bina Nusantara University, 2012)
Indonesian universities face internal and external challenges that need to be answered with the proper implementation of competitive strategy, especially for the development of organizational competencies needed in the future. This paper describes the importance of higher education having the competence of information and communication technology (ICT) which is strategic and operational as well as success indicators for the competency.